Synthesizing boron carbide powder from submicron-sized elemental boron and activated carbon and investigation of thermal oxidation behavior - Karaahmet, Oguz; Toy, Emre; Unluturk, Kumru Karaman; Cicek, Bugra (ELSEVIER SCIENCE SA, 2025)
Nano-sized boron carbide was synthesized using submicron elemental boron and activated carbon in B:C ratios of 4:1 and 8:1. Heat treatments were conducted at 1200-1600 degrees C, resulting in polyhedral nano-sized boron carbide. Crystallographic irregularities, including amorphous regions and peak intensity variations, were observed, particularly in samples with a higher boron ratio, likely due to boron penetration into the B4C structure or changes in crystallite size. Oxidation behavior, analyzed via thermal gravimetric analysis, showed that samples synthesized at 1300 degrees C had a lower oxidation onset temperature, indicating reduced thermal stability. SEM-EDS analysis identified the presence of a B2O3 layer on the surface, which decreased with rising temperature and acted as an oxidation barrier. Compared to commercial boron carbide, the synthesized powder demonstrated superior oxidation resistance up to 800 degrees C, despite showing greater weight gain during oxidation, likely due to particle size and impurities.
Keywords: Boron carbide; Elemental raw material; Synthesis; Nanoparticles; Oxidation resistance; Commercial powder; B4C; RESISTANCE; MORPHOLOGY; CERAMICS; DENSE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering